Notes to the underground: credit claiming and organizing in the Earth Liberation Front - Brown, Joseph M. (Terrorism and political violence, 2020)
This paper presents a case study of the Earth Liberation Front (ELF), based on interviews of the group’s former affiliates. It examines the role of credit claims in organizing this underground leaderless resistance group’s activity. In addition to the external signaling functions of credit claims—demonstrating capability, issuing demands, and soliciting public support—credit claims serve a movement-building role in the ELF. By issuing credit claims in “aboveground” fora that other cells are known to read, ELF cells with no direct links are able to communicate information to one another. Credit-claiming communiqués serve four organizing functions for the ELF. They constitute the ELF underground as an imagined community, recruit new cells, set agendas for future actions, and enforce operational standards of behavior via an informal “peer review” process. This study of the ELF suggests broader insights, including possible organizing techniques that may be observed in white supremacist and Islamist cases.